English Teachers' Perceptions of Curriculum Changes in Learning - Theresia Trines Anjelin Zai (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The curriculum is the most important thing in the world of education, the curriculum is used as a guide in the learning and teaching process. In this case the teacher has an important role in implementing the curriculum and determines the success or failure of delivering material to students. However, along with the erratic curriculum changes, there are many perceptions or complaints from English teachers about it. This is an important thing to discuss to find out the effectiveness of curriculum changes in Indonesia. The purpose of writing this journal is to find out the point of view of each teacher who specifically teaches English subjects towards curriculum changes in Indonesia. It also aims to find out what are the obstacles and advantages of the curriculum when implemented along with the impact of curriculum changes on the strategies or ways of teaching English teachers. The method used is a qualitative research method used to collect data through in-depth interviews with English teachers in several schools. the sources used in this research are journals, books, and other academic sources. Thus, this research can provide a better understanding of teachers' perspectives that play an important role in determining the success of curriculum change in learning.